A rare case of broad ligament fibroid in Mayer-Rokitansky-Küster-Hauser syndrome - Choudhary, Arpit; Takkar, Navneet; Kaur Pandher, Dilpreet; Satodiya, Mohit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Mayer-Rokitansky Kuster Hauser (MRKH) syndrome with lieomyoma is a rare disorder. Women with this syndrome have normal 46 XX karyotype, normal secondary sex characteristics and primary amenorrhea. There is a scarcity of cases in the literature where fibroid develops in women suffering from MRKH syndrome. Here, we present a case of an ectopic broad ligament fibroid found in a 41-year-old woman with MRKH syndrome type II. A 41-year-old married nulliparous female diagnosed with MRKH syndrome 20 years back, presented with an abdominal mass. Trans-abdominal ultrasound suggested a large mass on right side arising from paracolic area with heterogeneous echo texture. However, the ovarian vs leiomyoma origin of mass was of diagnostic dilemma. CEMRI confirmed the same findings and ruled out ovarian origin of the mass along with the presence of rudimentary uterus. Following this, the patient was taken for laparotomy followed by total abdominal hysterectomy with bilateral salpingoopherectomy, the fibroid was found to be arising from broad ligament and was removed along with the hypoplastic uterus and bilateral Fallopian tubes and ovaries. The case we presented exhibits the development of leiomyomas in patients with MRKH syndrome, although rare, is always a possibility and should be kept in mind as a differential diagnosis while evaluating an abdominopelvic mass. MRI is an accurate modality both for delineating the mass, confirming its origin as well as diagnosing MRKH syndrome.